Gertrude Bell queen of the desert, shaper of nations - Howell, Georgina 1942- (New York Farrar, Straus and Giroux, 2007)
She has been called the female Lawrence of Arabia, which, while not inaccurate, fails to give Gertrude Bell her due. She was at one time the most powerful woman in the British Empire: a nation builder, the driving force behind the creation of modern-day Iraq. Born into privilege in 1868, Bell turned her back on Victorian society, choosing to read history at Oxford and going on to become an archaeologist, spy, Arabist, linguist, author, poet, photographer, and mountaineer. She traveled the globe several times, but her passion was the desert--her vast knowledge of the region made her indispensable to the British government during World War I. As an army major on the front lines in Mesopotamia, she supported the creation of an autonomous Arab nation for Iraq, promoting and manipulating the election of King Faisal to the throne and helping to draw the borders of the fledgling state.--From publisher description.
Gertrude and Florence -- Education -- The civilized woman -- Becoming a person -- Mountaineering -- Desert travel -- Dick Doughty-Wylie -- Limit of endurance -- Escape -- War work -- Cairo, Delhi, Basra -- Government through Gertrude -- Anger -- Faisal -- Coronation -- Staying and leaving
"Originally published in 2006 by Macmillan, Great Britain, as Daughter of the desert"--T.p. verso.
Includes bibliographical references (p. [453]-460) and index.
UCWS-3344g donated by Adrienne Maguddayao - July 2019
Keywords: Bell, Gertrude Lowthian -- 1868-1926.; Travelers -- Middle East -- Biography; Women travelers -- Middle East -- Biography; Archaeologists -- Great Britain -- Biography; Women archaeologists -- Great Britain -- Biography; Asianists -- Biography; Women Asianists -- Biography; Colonial administrators -- Great Britain -- Biography; Colonial administrators -- Middle East -- Biography